1985
DOI: 10.1159/000265382
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Study of Water-Insoluble Fractions in Normal and Cataractous Human Lens Fibers

Abstract: Water-insoluble fractions of fiber cells from human transparent normal and opacified single lenses were compared ultrastructurally and by gel electrophoresis. Intermediate-sized filaments which had been clearly shown in aged transparent normal cortices, virtually vanished in the opacified nuclei in contrast to microfilaments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…With regard to actin, other investigators have suggested that this cytoskeletal protein may not be required for any specific function in the compacted nuclear fiber cells . Although an accelerated loss of vimentin has been reported to occur in the nucleus of human nuclear cataracts (Ozaki, Jap and Bloemendal, 1985), a finding similar to the results of this study with HBO, vimentin-knockout mice, surprisingly, have been found to possess a normal lens cortex and nucleus (Colucci-Guyon et al, 1994). Regarding lens cortical changes, HBO-treatment produced no increased scatter or loss of cytoskeletal proteins in that region.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…With regard to actin, other investigators have suggested that this cytoskeletal protein may not be required for any specific function in the compacted nuclear fiber cells . Although an accelerated loss of vimentin has been reported to occur in the nucleus of human nuclear cataracts (Ozaki, Jap and Bloemendal, 1985), a finding similar to the results of this study with HBO, vimentin-knockout mice, surprisingly, have been found to possess a normal lens cortex and nucleus (Colucci-Guyon et al, 1994). Regarding lens cortical changes, HBO-treatment produced no increased scatter or loss of cytoskeletal proteins in that region.…”
Section: Discussionsupporting
confidence: 84%
“…Typically, the content of cytoskeletal proteins in the lens decreases with age, particularly in the nucleus. Loss of these proteins, including vimentin and α-actinin, has been observed to accelerate in the human lens during the development of senile cataract (Ozaki, Jap and Bloemendal, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…35 Stable peptides of about 66 kDa 46 or 53 kDa 35 and smaller (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) 35,46 are produced in an age dependent fashion. Peptides of these sizes were recognized by the polyclonal antibody to filensin used here, and likely represent these proteolytic products.…”
Section: Discussionmentioning
confidence: 99%
“…22 Furthermore, decreased content of cytoskeletal proteins has been reported for human cataracts. 23,24 These studies underscore the importance of the integrity of the lens cytoskeletal structures. However, little information is available about the interaction of these cytoskeletal elements with the lens plasma membrane, or how these interactions change during maturation and aging.…”
Section: Introductionmentioning
confidence: 91%
“…Typically, the concentration of cytoskeletal proteins in the lens decreases with age, particularly in the nucleus. Loss of these proteins, including vimentin and α-actinin, is accelerated in the human lens during the development of senile cataract [14,21]. Understanding the precise role of these proteins is critical for characterizing the putative malfunctions in molecular cascades that lead to cataracts, and could potentially provide useful information for the development of therapies that retard or prevent cataractogenesis.…”
Section: Introductionmentioning
confidence: 99%